Understanding the relationship between natural resources, renewable energy consumption, economic factors, globalization and CO2 emissions in developed and developing countries. (26th May 2021) - Muhammad, Bashir; Khan, Sher
Abstract: This study is not only important for policy creators but also useful for governments of both developed and developing countries in which to improve their carbon dioxide (CO2 ) emissions and also to maintain growth in renewable electricity production. This study is concerned with the impact that renewable energy consumption, economic factors, globalisation and natural resources have on CO2 emissions in 31 developed and 155 developing countries over the period 1991 to 2018, and utilises time pair dynamic fixed effect and time pair dynamic generalised method of moments (GMM) and system generalised method of moments (system GMM) estimators. The results indicate that renewable energy and social globalisation play a very important role in a CO2 emission reduction of both developed and developing countries. Moreover, in developed countries fuel exports, economic growth, and economic globalisation increase CO2 emissions. Although in developing countries, fuel exports and economic globalisation reduce CO2 emissions, and economic growth and political globalisation increase CO2 emissions. Therefore, policy implications are suggested for both the developed and developing countries' not only for environmental reasons, but also for sustaining growth in fuel exports and for increasing renewable electricity.